Effect of COVID-19 on Maintaining Balance in Highly Skilled Handball Players. - Fernández-Rodríguez, Emilio; Niznikowski, Tomasz; Romero-Ramos, Óscar; Markwell, Logan (University of Physical Education in Warsaw, 2023)
Introduction. The aim of this study was to evaluate the effect of COVID-19 on maintaining balance in highly skilled handball players during the performance of the modified Romberg test. Material and Methods. As part of a larger investigation that was initiated in 2019, twelve professional handball players were recruited to participate in a study that was designed to measure static balance performance. Following the initial pre-test, six participants (body height 184.8 ± 4.7 cm; body weight 85.5 ± 3.3 kg; age 21.3 ± 1.2 years) contracted COVID-19. The remaining six participants (body height 188.7 ± 2.6 cm; body weight 92.3 ± 3.7 kg; age 26.3 ± 3.3 years) never tested positive for COVID-19 and pre-sumably were not infected with the virus. The experimental design required all participants to complete an initial balance assessment (pre-test) and a later balance assessment (post-test). To fully analyze our data, we conducted a 2 (condition: COVID, no-COVID) X 2 (test: pre-test, post-test) ANOVA with repeated measures on the second factor. Results. Our research results showed that the skilled handball players who contracted COVID-19 mani-fested a significant decrease in balance performance from the pre-test which occurred prior to being infected with COVID-19 relative to the post-test which occurred following the COVID-19 infection. Conclusions. In conclusion, the results we have reported here are the first to show an objectively measured association between COVID-19 and the ability to maintain balance. Further intensive multifaceted research on this issue is needed.
Keywords: Deportistas - Enfermedades; COVID-19; handball players